2015
DOI: 10.1146/annurev-publhealth-032013-182516
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Effects of Environmental and Policy Change Interventions on Healthy Eating

Abstract: Obesity has been characterized as a disease. Strategies to change the incidence and prevalence of this disease include a focus on changing physical and social environments, over and above individual-level strategies, using a multilevel or systems approach. We focus our attention on evidence published between 2008 and 2013 on the effectiveness of interventions in nutrition environments, i.e., environmental interventions designed to influence the intake of healthful foods and amount of energy consumed. An overar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 94 publications
(179 reference statements)
1
42
0
Order By: Relevance
“…Following our review of validation studies (2), we purchased food store data from InfoUSA and fast food restaurant data from Dun & Bradstreet. After cleaning the home address geocodes and retail food outlet data in order to maximize their accuracy and utility (e.g., reclassifying some records by store type, deduplicating records)(2), we constructed annual (4 th quarter) measures of the geographic accessibility of chain supermarkets [standard industrial classification (SIC) codes 541101-541109 (excluding 541103, convenience stores) and >$2M annual sales, or name listed in Supermarket News Top 75 Retailers and Wholesalers in any year between 2010 and 2014]; non-chain supermarkets [SIC codes 541101-541109 (excluding 541103) and >$2M annual sales but name not listed in Supermarket News]; supercenters and other non-membership mass merchandisers (SIC code 53 and Walmart, Kmart, Target, or Meijer in name); chain fast food restaurants including pizza [SIC code 58120601 or 581203 and name listed in National Restaurant News Top 200 between 2007 and 2013 or name listed in Quick Service or Fast Casual or Quick Service Restaurant Top 50 between 2007 and 2013 (but not coffee shops: 58120304)]; and non-chain fast food restaurants (SIC code 58120602 or 581203 and name not in National Restaurant News or Quick Serve Restaurant lists).…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Following our review of validation studies (2), we purchased food store data from InfoUSA and fast food restaurant data from Dun & Bradstreet. After cleaning the home address geocodes and retail food outlet data in order to maximize their accuracy and utility (e.g., reclassifying some records by store type, deduplicating records)(2), we constructed annual (4 th quarter) measures of the geographic accessibility of chain supermarkets [standard industrial classification (SIC) codes 541101-541109 (excluding 541103, convenience stores) and >$2M annual sales, or name listed in Supermarket News Top 75 Retailers and Wholesalers in any year between 2010 and 2014]; non-chain supermarkets [SIC codes 541101-541109 (excluding 541103) and >$2M annual sales but name not listed in Supermarket News]; supercenters and other non-membership mass merchandisers (SIC code 53 and Walmart, Kmart, Target, or Meijer in name); chain fast food restaurants including pizza [SIC code 58120601 or 581203 and name listed in National Restaurant News Top 200 between 2007 and 2013 or name listed in Quick Service or Fast Casual or Quick Service Restaurant Top 50 between 2007 and 2013 (but not coffee shops: 58120304)]; and non-chain fast food restaurants (SIC code 58120602 or 581203 and name not in National Restaurant News or Quick Serve Restaurant lists).…”
Section: Designmentioning
confidence: 99%
“…In recent years, various levels of government in the U.S. have adopted or discussed subsidies, tax breaks, zoning laws, and other public policy instruments to promote geographic access to healthy food(1,2). For example, healthy food financing initiatives offer subsidies and tax breaks to open new stores or renovate existing stores in underserved areas(1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Bowen et al . recently completed a critical literature review, guided by a socioecological framework, on the effects of different types of environmental and policy interventions on healthy eating, from a US perspective. They concluded that, whilst the evidence reviewed did not support menu labelling as an effective strategy to change purchasing patterns, additional strategies to enhance menu labelling practices, and strategies beyond labelling (including implementation of nutritional standards), may be useful.…”
Section: Introductionmentioning
confidence: 99%
“…The marketplace for snacks is affected by many factors including authenticity, familiarity, current trends, packaging and competition [16] and there is a high risk of "failure". However with increased calls for reduction of intake of added sugar [17] , policies in hospitals and public institutions about healthier food environments [18] and rising demand from consumers for healthier options in snack foods [19,20] a case may also be made for development of products to fit a required nutrition profile and to have substantiated health claims that are part of the marketing approach [21] . The lack of preservatives and additives meant that the bar had to be baked longer to remove free water and initially was perceived as dry by some consumers.…”
Section: Resultsmentioning
confidence: 99%